Desenvolvimento dependente latino-americano no século XXI: desigualdade e padrão de reprodução - Araujo, Priscila Santos de (2013)
This thesis supports basically the existence of inequality in capitalist system structure. This inequality is constitutive of historical determinations of capitalist social formations, which are organically formed into a global, hierarchical and combined system which tends to reproduce itself. The main focus is towards Latin-American social formations, their nature and global insertion. The motivation of choosing this theme arose when the World Bank presented, in 2011, an interpretation of the evolution of the Subprime Crisis. The defended idea pointed to a significant change in worldwide economy structure when several developing economies assumed leadership roles in determining the overall dynamics. Our argument is a different one, recovering main elements of Marx s interpretation concerning to capitalism nature as well other authors on Marxist Dependence Theory, who developed and deepened these propositions in their concrete treatment of Periphery. Thus, the aim of this study is to discuss the nature of Latin American dependent development as an offshoot of the unequal structure of the world capitalist system. In the context of contemporary capitalism, there is no modification in the international condition of Latin American economies, because they are countries that fuel the capitalism of the central system at the same time that they are conditioned to it. In the current phase, no longer exclusively providers of raw materials because their diversified industry, but remained essentially a reproduction pattern guided in exports of primary goods complementing them with more sophisticated ones. These elements keep a limited internal dynamic, as a form of compensation for such transfer remains by overexploitation, saving the difficulties of realization of production value. Given this situation, we indicate that remains the organist capitalism system as well a social and economic inequality intrinsic to peripheral economies. This is the nature of Latin-American dependent economies. So that, from the open trail proposed by theoreticians of Marxist Theory of Dependency, this thesis contests the approach from dominant field of Economy that highlights the advances of capitalism and conceal their mishaps, such achievements opened to all.